English Language Teachers’ Perception and Management of Learners’ Oral Communication Apprehension - Mohd Nor Jettey, Annisa Nor Jettey (2006)
This study reports on how English language (EL) teachers perceive and manage oral communication apprehension (CA) among learners in the language classrooms. The main purpose of this qualitative study was to understand language teachers’ perception and how they think they are addressing the phenomenon. This study reports on how teachers operate in the language classrooms in relation to learners’ fear of oral communication and how they manage it. Additionally, the issues and problems that have emerged in relation to oral language development in general will be presented and discussed. A qualitative methodology was employed to explore the respondents at their natural setting. The data generated through interviews, classroom observations and document reviews were able to capture the teachers’ thoughts, teaching and management of learners in relation to the phenomenon in five Malaysian secondary schools. A total of twelve respondents were involved in this study. They comprised eight English language teachers, one principal and three heads of the English language department. The teachers are the primary respondents. These teachers shared their thoughts, experiences and perceptions on the phenomenon. The data from the primary respondents were triangulated with the secondary respondents, the principal and the heads of the language department. The data were analyzed manually by coding and categorizing them based on common patterns that emerged. The study found that teachers are perceptible of learners’ manifestations, which indicated that the learners are oral communication apprehensive. The findings confirmed some of the manifestations mentioned in earlier literature and at the same time present new information. It is interesting to note that Malaysian EL teachers are also sensitive to learners’ emotive disposition at oral communication. However, their perceptibility of learners’ fear of oral communication was not reflected in their pedagogical practices due to ‘constraints’. The findings too revealed EL teachers’ view of oral CA learners. This is another new finding as no previous study investigated teachers’ views concerning the issues in the language classrooms. Findings illustrated that teachers’ views were influenced by their perception of oral language development. This study confirmed earlier findings on the implementation of the language curriculum, that teachers do not put emphasis on oral language development. It also found that oral language was carried out as a ‘by-product’ towards achieving other language skills namely reading and the writing skills. Since oral language is not given emphasis in the language class, consequently, teachers do not give attention to oral CA and oral CA learners are marginalized. The study managed to uncover the rationale behind teacher’ actions in the classrooms. The teachers’ working practical knowledge emerged from the demands teachers felt that were imposed on them. At the top of the demands list was that teachers have to produce results in examinations. Further investigation revealed that oral language does not play a part in the determination of grades, thus the development of the speaking skill was not given equal emphasis in the language classrooms and thus further marginalizing oral CA learners. This study has implication on theory and practice of managing oral CA learners. It is recommended that a review of teaching and assessment is conducted.